From Conflict to Peace: Fuqaha Political Exegesis on Israel's War Crimes in Palestine - Basid, Abdul (Institut Agama Islam Negeri Curup, 2024)
The aims of this research are to analyse the contributions of Indonesian netizens' comments regarding Israel's war crimes in Palestine and to examine the contributions of fuqaha's political exegesis towards peace politics in addressing these crimes. The study provides insights into Indonesian netizens' views and the role of fuqaha in promoting sustainable peace. Using an in-depth qualitative method and textual analysis, the research focuses on fuqaha interpretations of Israel's war crimes, the two-state solution, Palestinian independence, and the role of Islamic law in peace and reconciliation. Participants include fuqaha experts, Islamic studies and international law academics, and Indonesian netizens selected for their expertise. Data collection involves analyzing war crimes documents, two-state resolution texts, and public forum comments. Thematic coding identifies patterns in the data. Findings show Indonesian netizens' strong opinions on social media, calling for accountability for figures like Netanyahu and urging ICC action. Fuqaha, like Al-Shafi'i, Al-Shaukani, and Al-Zuhaily, emphasise peace and justice, condemning Israel's violations of international law. They advocate for integrating Islamic principles into political and social approaches to achieve lasting peace.